Nexus Between Spermidine and Floral Organ Identity and Fruit/Seed Set in Tomato - Nambeesan, Savithri U.; Mattoo, Autar K.; Handa, Avtar K. (Frontiers in Plant Science, 2019)
Polyamines (PAs) constituting putrescine (Put), spermidine (Spd), and spermine (Spm) are ubiquitous in all organisms and play essential roles in the growth and developmental processes in living organisms, including plants. Evidences obtained through genetic, biochemical, and transgenic approaches suggest a tight homeostasis for cellular PA levels. Altered cellular PA homeostasis is associated with abnormal phenotypes. However, the mechanisms involved for these abnormalities are not yet fully understood, nor is it known whether cellular ratios of different polyamines play any role(s) in specific plant processes. We expressed a yeast spermidine synthase gene (ySpdSyn) under a constitutive promoter CaMV35S in tomato and studied the different phenotypes that developed. The constitutive expression of ySpdSyn resulted in variable flower phenotypes in independent transgenic lines, some of which lacked fruit and seed set. Quantification of PA levels in the developing flowers showed that the transgenic plants without fruit and seed set had significantly reduced Spd levels as well as low Spd/Put ratio compared to the transgenic lines with normal fruit and seed set. Transcript levels of SlDELLA, GA-20oxidase-1, and GA-3oxidase-2, which impact gibberellin (GA) metabolism and signaling, were significantly reduced in bud tissue of transgenic lines that lacked fruit and seed set. These findings indicate that PAs, particularly Spd, impact floral organ identity and fruit set in tomato involving GA metabolism and signaling. Furthermore, we suggest that a nexus exists between PA ratios and developmental programs in plants.